Agro-morphological Characterization of Cactus Pear Accessions for Fodder Purposes in Arid Gujarat - Naorem, Anandkumar; Patel, Sachin; Dayal, Devi (Annals of Arid Zone, 2023)
Belonging to the cactaceae family, Opuntia ficus-indica, popularly known asprickly pear or cactus pear has been recommended as a drought-resilient arid crop. InKachchh, an arid zone in the western part of India, Opuntia ficus-indica has been increasingcultivated as a fodder resource, mainly for its water-rich cladodes. In this regard, sixty-two accessions of cactus pear were collected from ICAR-CAZRI, Kukma and ICARDAand were maintained in ICAR-CAZRI, RRS-Bhuj. To conduct an agro-morphologicalstudy aiming to understand the growth behaviour of these cactus accessions underarid soils and the climate of Kachchh, nine phenotypic characteristics were recorded.Based on the quantitative traits, the results of PCA showed three groups of cactusaccessions based on their growth performance. The best five accessions selected forpromotion in the Kachchh region were CAZRI Botanical Garden (CBG), No. 1270, No.1271, No. 1308 and Bianca Macomer. Although CBG performs the best out of all theseaccessions, proper care must be taken to avoid waterlogging in and around the rootzones of CBG. Therefore, cactus pear can be successfully cultivated as a fodder cropin arid Kachchh and can address the unavailability of green fodder in dry seasons andpoor soils of Kachchh.